Cysteines 208 and 241 in Ero1α are required for maximal catalytic turnover - Ramming, Thomas (Redox Biol, 2015)
Endoplasmic reticulum (ER) oxidoreductin 1α (Ero1α) is a disulfide producer in the ER of mammalian cells. Besides four catalytic cysteines (Cys(94), Cys(99), Cys(394), Cys(397)), Ero1α harbors four regulatory cysteines (Cys(104), Cys(131), Cys(208), Cys(241)). These cysteines mediate the formation of inhibitory intramolecular disulfide bonds, which adapt the activation state of the enzyme to the redox environment in the ER through feedback signaling. Accordingly, disulfide production by Ero1α is accelerated by reducing conditions, which minimize the formation of inhibitory disulfides, or by mutations of regulatory cysteines. Here we report that reductive stimulation enhances Ero1α activity more potently than the mutation of cysteines. Specifically, mutation of Cys(208)/Cys(241) does not mechanistically mimic reductive stimulation, as it lowers the turnover rate of Ero1α in presence of a reducing agent. The Cys(208)/Cys(241) pair therefore fulfills a function during catalysis that reaches beyond negative regulation. In agreement, we identify a reciprocal crosstalk between the stabilities of the Cys(208)–Cys(241) disulfide and the inhibitory disulfide bonds involving Cys(104) and Cys(131), which also controls the recruitment of the H(2)O(2) scavenger GPx8 to Ero1α. Two possible mechanisms by which thiol–disulfide exchange at the Cys(208)/Cys(241) pair stimulates the catalytic turnover under reducing conditions are discussed.